2006
DOI: 10.1097/00005721-200609000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Capturing Children??s Voices for Quality Improvement

Abstract: Children's unique perspectives should be sought regularly and their data included in ongoing programs of quality assessment. When only parents are queried, important and insightful perspectives of children are missed that could improve care quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(77 citation statements)
references
References 7 publications
4
66
0
7
Order By: Relevance
“…Fear of losing control over one's body and being injured causes great distress for children, constituting the core experience in pain and medical operations (Gross and Gardner, 1980). Lindeke et al (2006) cited children's pain and discomfort as the worst aspects of hospitalization.…”
Section: Pain and Expression Of Pain-related Emotionsmentioning
confidence: 99%
“…Fear of losing control over one's body and being injured causes great distress for children, constituting the core experience in pain and medical operations (Gross and Gardner, 1980). Lindeke et al (2006) cited children's pain and discomfort as the worst aspects of hospitalization.…”
Section: Pain and Expression Of Pain-related Emotionsmentioning
confidence: 99%
“…One child described intense fear of the "doctors and what they had in their pockets" whenever they came near the room, expecting a "stick" from them, although the child was not anticipating another "shot" other than the first one. Consistent with findings with hospitalized children (Carney et al, 2003;Koening et al, 2003;Lindke et al, 2006;Salmela et al, 2009;, children in both age groups reported fear of pain (surgical and needles) or procedures.…”
Section: Discussion Of Findingssupporting
confidence: 84%
“…Children of all ages reported fear of pain (needles) and procedures (Carney et al, 2003;Koening, Chesla, & Kennedy, 2003;Lindke, Nakai, & Johnson, 2006;Salmela, Salanterä, & Aronen, 2009;.…”
Section: Picu Environment Stressors and Memoriesmentioning
confidence: 99%
See 2 more Smart Citations